CHEMISTRY AND BIOLOGICAL EVALUATION OF CAMEROONIAN DORSTENIA SPECIES - Ngadjui, B.; Bezabih, M.; Abegaz, B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Research in the area of natural products is an important scientific activity in Cameroon where a large variety of plants, especially, Dorstenia spp are used as anti-snakebite, anti-infection and anti-rheumatism remedies in medicinal plant therapy. The genus is recognized as a rich source of prenyl and geranyl-substituted coumarins and flavonoids [1]. There is now increasing interest in this genus. Almost 40 papers have appeared during the last decade, reporting on research results on over 25 Dorstenia species. As part of our program to study the chemical constituents of African Dorstenia species [1] we have investigated 14 species from Cameroon. More than hundred secondary metabolites, of which thirty are new derivatives, were isolated using various chromatographic techniques (VLC, CC, PTLC), and characterized using extensive spectroscopic methods. These compounds are regrouped into: triterpenoids, styrenes, coumarins and mainly flavonoids [1]. 3, 3’- bis [3, 7-Dimethyl-2, 6-octadienyl]-4, 5, 2’, 4’-tetrahydroxylchalcone, isolated from the twigs of D. prorepens, is the first example of a bis-geranylated chalcone. Eleven diprenylated flavonoids have so far been isolated from Dorstenia and all of them are reported to be isolated from the twigs of D. mannii [1]. D. psilurus provided triprenylated flavonoids with two units in ring A and one in ring B [1]. The pharmacological data of this genus is scanty. Extracts and/or compounds from the investigated species show anti-inflammatory, analgesic, anti-oxidant and antimalarial activities [2]. Inhibition of matrix-metalloproteinase-2 secretion from brain tumour cells suggests chemo-preventive properties of furanocoumarin glucoside and chalcones isolated from D. turbinata [3]. To the best of our knowledge, prenylated flavonoids have only been reported from African Dostenia species so far. References:[1] Abegaz B.M., Ngadjui B.T et al. 2000, Current Organic Chemistry, 4, 1079-1090. [2] Ngameni B., Watchueng J. et al., 2007, Arkivoc (XIII) 116-123 [3] Ngameni B. Touaibia M. et al, 2007, Phytochemistry, 67, 2573-2579